A geography of Pennsylvania (Pennsylvania State University Press, 1995)
The culture and economy of Pennsylvania have been developing for more than 300 years. As a consequence, human activities have evolved from those based on primary occupations in the eighteenth century to the manufacturing economy of the nineteenth and early twentieth centuries to the tertiary functions of the late twentieth century. With each major change in economic structure the geographic patterns also changed. The Geography of Pennsylvania charts those changes and provides a spatial analysis of each key geographic function taking place in the state. This book will be an indispensable reference for those who want to understand the factors that shaped Pennsylvania into the dynamic society it is today.